Holonic Workforce Allocation To Reduce The Impact Of Absenteeism And Turnover - Lim , Yong Ching (2011)

(untitled)
Holonic Manufacturing System (HMS) adopts Arthur Koestler’s generalisation on living organisms and social organisations into a novel paradigm that suits the manufacturing industry. Autonomy and cooperation are the prime attributes of holons. The holonic concepts have been applied to many areas, and yet, rarely attempted on workforce allocation. Hence, this scientific research is intended to develop a duallevel advisory model called Holonic Workforce Allocation Model (HWM) in order to deal with absenteeism and turnover.